Outcomes for transformed follicular lymphoma in the rituximab era: the Royal Marsden experience 2003–2013. Issue 8 (3rd August 2017) - Gleeson, Mary; Hawkes, Eliza A.; Peckitt, Clare; Wotherspoon, Andrew; Attygalle, Ayoma; Sharma, Bhupinder; Du, Yong; Ethell, Mark; Potter, Mike; Dearden, Claire; Horwich, Alan; Chau, Ian; et al.
Abstract: Survival for transformed follicular lymphoma (tFL) has improved in the rituximab era and the need for upfront stem cell transplantation (SCT) is unclear. We evaluated the outcomes for all patients treated with first-line chemotherapy for histologically-proven tFL at our institution from 2003–2013 ( n  = 87). The majority of patients (89.7%) did not receive a SCT as part of first-line management. With a median follow-up of 7.8 years the 5-year overall survival (OS) for all patients was 61.7%. Patients treated with R-CHOP without upfront SCT ( n  = 55/87) had a 5-year OS of 64.3%. In a Cox regression analysis of the entire cohort ( n  = 87) International Prognostic Index (IPI) risk group and presence of B symptoms at transformation were independently associated with OS in multivariate analysis (MVA). Our analysis confirms the improved survival of tFL in the rituximab era even in the absence of upfront SCT consolidation.